The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11628-009-0088-0
|View full text |Cite
|
Sign up to set email alerts
|

The appealing characteristics of download type mobile games

Abstract: As the mobile game industry enjoys continual and rapid growth in the market and becomes a major sector of the service industry, it is of great interest to examine the very features that make mobile games so fascinating and keep its players coming for more. Pinpointing more precisely the very factors that increase the attraction of games will help game makers allocate corporate resources more efficiently. In addition, a more in depth analysis of the appealing characteristics enable game producers to establish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
(47 reference statements)
0
13
1
Order By: Relevance
“…We examined the Chi-square, the Normed Fit Index (NFI), the Comparative Fit Index (CFI), and the Root Mean Square Error of Approximation (RMSEA) for the overall model. The estimated values of these parameters were higher than the cutoff levels suggested in the literature (Kim et al 2009), suggesting that our model was valid at a level of significance greater than 0.05. The NFI value for our model was 0.8860 and CFI as 0.8690.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We examined the Chi-square, the Normed Fit Index (NFI), the Comparative Fit Index (CFI), and the Root Mean Square Error of Approximation (RMSEA) for the overall model. The estimated values of these parameters were higher than the cutoff levels suggested in the literature (Kim et al 2009), suggesting that our model was valid at a level of significance greater than 0.05. The NFI value for our model was 0.8860 and CFI as 0.8690.…”
Section: Discussioncontrasting
confidence: 66%
“…1-6), we performed a path analysis (Kim et al 2009) on the model shown in Fig. 1 using Maximum Likelihood Estimation (MLE) estimation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, downloading apps has usually been studied in relation to pirate behaviors, and mobile games are not exempt from this ( Phau & Liang, 2012 ), which may offer a partial explanation for why downloading apps predicted prohibited smartphone use. Another explanation may be the social element to downloading apps (e.g., sharing results with others; Kim, Oh, Yang, & Kim, 2010 ). These two motivations for downloading apps hold for free-to-play Facebook games, which are easy and convenient, playable with friends, and as single players ( Kuo-Hsiang, Shen, & Min-Yuan, 2012 ; Paavilainen, Hamari, Stenros, & Kinnunen, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in wireless communication technology have increased the use of mobile devices and also accelerated the development of mobile services [1]. Especially, mobile service business has entered a new era with the advent of mobile devices with new features and the evolution of the mobile app ecosystem since the Apple App Store launched on July 10, 2008.…”
Section: Introductionmentioning
confidence: 99%